Choroid plexus perfusion in sickle cell disease and moyamoya vasculopathy: Implications for glymphatic flow. Issue 10 (October 2021) - Johnson, Skylar E; McKnight, Colin D; Jordan, Lori C; Claassen, Daniel O; Waddle, Spencer; Lee, Chelsea; Garza, Maria; Patel, Niral J; Davis, L. Taylor; Pruthi, Sumit; Trujillo, Paula; Chitale, Rohan; et al.
Cerebrospinal fluid (CSF) and interstitial fluid exchange have been shown to increase following pharmacologically-manipulated increases in cerebral arterial pulsatility, consistent with arterial pulsatility improving CSF circulation along perivascular glymphatic pathways. The choroid plexus (CP) complexes produce CSF, and CP activity may provide a centralized indicator of perivascular flow. We tested the primary hypothesis that elevated cortical cerebral blood volume and flow, present in sickle cell disease (SCD), is associated with fractionally-reduced CP perfusion relative to healthy adults, and the supplementary hypothesis that reduced arterial patency, present in moyamoya vasculopathy, is associated with elevated fractional CP perfusion relative to healthy adults. Participants (n = 75) provided informed consent and were scanned using a 3-Tesla arterial-spin-labeling MRI sequence for CP and cerebral gray matter (GM) perfusion quantification. ANOVA was used to calculate differences in CP-to-GM perfusion ratios between groups, and regression analyses applied to evaluate the dependence of the CP-to-GM perfusion ratio on group after co-varying for age and sex. ANOVA yielded significant (p < 0.001) group differences, with CP-to-GM perfusion ratios increasing between SCD (ratio = 0.93 ± 0.28), healthy (ratio = 1.04 ± 0.32), and moyamoya (ratio = 1.29 ± 0.32) participants, which was also consistent with regression analyses. Findings are consistent with CP perfusion being inversely associated with cortical perfusion.